The bacteria of compressed yeast - Colliver, Mary P. (My University, 1905)
Introduction: Yeast is one of the most interesting substances used in the household, and one that is usually but little understood. The knowledge resulting from even a superficial study will more than repay the effort by a gain in uniformity of results following its use. The yeast plant is one of the simplest forms of vegetable life, consisting of a single cell microscopic in size. It belongs to the class of fungi and feeds only upon organic material. Under certain conditions unfavorable to the best development of the plant it Col= spores which are fitted to withstand drying and live for some time in a quiescent state. These spores are widely distributed, being found in the surface of the Ground, and for two or three inches beneath the surface as well as on nearly all fruits and vegetables. Many varieties of yeast have been studied and described but only two or three are cultivated. The yeast plant has been most carefully studied with respect to its power in producing alcohol, in breweries and distilleries. And much of the compressed yeast on the market is a by-product of such plants. There are, however, large establishments which make compressed yeast their principal product. In the process of manufacturing compressed yeast the grain is carefully selected and washed. After crushing a part of it is flowed to sprout, forming malt. Lactic acid is also allowed to form as a small amount of this acid serves as a protection against bacterial growth. To the entire amount of grain an abundance of eater is added as the yeast requires a liquid medium for its best development. Almost as soon as the seed yeast is son fermentation begins.
Citation: Colliver, Mary P. The bacteria of compressed yeast. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Yeast; Manufacture of Yeast; Infection of Yeast; Theses